2019
DOI: 10.1155/2019/8312020
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Bushen Antai Recipe Upregulates Estrogen and Progesterone Receptors at the Maternal-Fetal Interface in Pregnant Rats with Mifepristone-Induced Pregnancy Loss

Abstract: Background The modified Bushen Antai recipe (BSAT) is a centuries-old traditional Chinese medicine that we use in our center as a therapy against pregnancy loss. Our study aimed to explore the potential benefit and mechanism of BSAT in pregnant rats with mifepristone-induced pregnancy loss. Materials and Methods The signature compounds of the eight BSAT ingredients were analyzed by high-performance liquid chromatography (HPLC). The BSAT group (n = 8) was treated daily with 6.3 ml/kg BSAT from gestation day (D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…P is the main biologically active progestin secreted by the ovary that binds to specific receptors in target tissues such as the endometrium and myometrium to maintain placental function [ 18 ]. It is also able to reduce the sensitivity of the uterine muscle to contraction to avoid abnormal uterine contractions during pregnancy [ 19 ]. E2 is an estrogen secreted by the placenta and ovaries, which can promote endometrial proliferation and lay the foundation for normal pregnancy, and its level in early pregnancy can reflect ovarian luteal function and the quality of the dominant follicle [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…P is the main biologically active progestin secreted by the ovary that binds to specific receptors in target tissues such as the endometrium and myometrium to maintain placental function [ 18 ]. It is also able to reduce the sensitivity of the uterine muscle to contraction to avoid abnormal uterine contractions during pregnancy [ 19 ]. E2 is an estrogen secreted by the placenta and ovaries, which can promote endometrial proliferation and lay the foundation for normal pregnancy, and its level in early pregnancy can reflect ovarian luteal function and the quality of the dominant follicle [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al [62] proposed that Dipsaci radix and its main ingredient, akebia saponin D, may promote decidualization in pregnant women. Bushen Antai, a Chinese herbal medicine preparation containing Dipsaci radix, was found to reduce the pregnancy loss caused by mifepristone administration [183]. This preparation may stimulate estrogen and progesterone receptors through Akt and Erk1/2 signaling pathways in the maternal-fetal interface of pregnant rats.…”
Section: Othersmentioning
confidence: 99%
“…YKOL combined with conventional therapy for TMFP: A protocol for systematic review and meta-analysis and improving the live birth rate [17]. The reported mechanisms from modern researches of YKOL various components are as follows: Semen Cuscutae Chinensis and Dipsacales are reported to have steroid-like and hormone-like effects, maintaining the hormone balance of the pregnant mother [15]; Cibotii Rhizoma maintain immune balance [18]; Asini Corii Colla, which has always been used as a tonic, promotes blood circulation [19].…”
Section: Plos Onementioning
confidence: 99%
“…This effect is related to increasing the hormone levels of follicle stimulating hormone, luteinizing hormone, prolactin, progesterone, and estrogenic in serum and promoting the proteins expression of prolactin receptor, progesterone receptor, and estrogenic receptor in mouse decidua [ 13 – 16 ]. In addition, animal studies also have found that YKOL may induce estrogen and progesterone receptors by phosphorylation via the classic Akt and Erk1/2 signaling pathways in the maternal-fetal interface of pregnant rats, thereby reducing the pregnancy loss rate and improving the live birth rate [ 17 ]. The reported mechanisms from modern researches of YKOL various components are as follows: Semen Cuscutae Chinensis and Dipsacales are reported to have steroid-like and hormone-like effects, maintaining the hormone balance of the pregnant mother [ 15 ]; Cibotii Rhizoma maintain immune balance [ 18 ]; Asini Corii Colla , which has always been used as a tonic, promotes blood circulation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%